(untitled) (Zaporizhzhia Historical Review, 2021)
During the XIX ñ XX centuries in polish historiography the discussion between two main positivistís historical schools of thought ñ the Krakow and the Warsaw ñ was expanded. They were ruled over by neoromantic and modernistís schools, which were more corresponding to the standard of those days scholarship and social and political realities.